Manajerial Kepala Madrasah dalam Meningkatkan Kompetensi Guru di MA An Nawari Desa Seratengah Kecamatan Bluto Kabupaten Sumenep - A. Faisol Amir; Ashari Ashari (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
In this study, researchers used a qualitative descriptive method with data collection techniques of participant observation, interviews, and documentation. Meanwhile, the collected data was analyzed using the Miles and Huberman data analysis model, namely through 4 stages: data collection, data reduction, data presentation, and drawing conclusions. The subjects in this study were the head and teachers. While the location of this research was carried out at MA An Nawari Serattengah Bluto, Sumenep.Based on the analysis of the data, the answer was that the managerial head of MA An Nawari uses several very broad aspects, starting from preparing school plans, developing the organization, providing directions, and carrying out supervision of the implementation of school activities according to applicable supervisory standards. The management of the madrasa head is very influential in increasing the competencies that must be possessed by teachers, both personality competencies, pedagogic competencies, social competencies, and professional competencies which will have implications for improving the quality of education in general.